2020
DOI: 10.1145/3377873
|View full text |Cite
|
Sign up to set email alerts
|

Should I Stay or Should I Go

Abstract: To improve the user engagement, especially under moderate to high traffic demand, it is important to understand the impact of the network and application QoS on user experience. This article comparatively evaluates the impact of impairments, with emphasis on rebufferings, startup delay, and bitrate changes, and their intensity and temporal dynamics, on user engagement in the context of video streaming. The analysis employed two large YouTube datasets. To characterize the user engagement and the impact of impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In this study, we indicate that QoS impairments are a key element impacting the recommendation system context, and provide a systematic way to quantify its effect on QoE. Virtual QoS impairments may be due to content that is out of cache, and in that sense are similar to impairments due physical items being out of stock [41].…”
Section: B Context-aware and Multi-criteria Recommendersmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, we indicate that QoS impairments are a key element impacting the recommendation system context, and provide a systematic way to quantify its effect on QoE. Virtual QoS impairments may be due to content that is out of cache, and in that sense are similar to impairments due physical items being out of stock [41].…”
Section: B Context-aware and Multi-criteria Recommendersmentioning
confidence: 89%
“…In [41], [42] the authors considered user engagement as their target QoE metric. In particular, in [42] the authors accounted for users' interests and QoS factors to build an engagement/QoE predictive model.…”
Section: A Qos and Qoe Parametersmentioning
confidence: 99%
“…Recently, published papers that focus on user engagement identified a correlation of video quality and network performance with engagement metrics. 26…”
Section: Video Qoe Predictionmentioning
confidence: 99%
“…Takahashi et al 25 studied the impact of quality factors such as stalling, initial delay, and average bitrate on the cumulative quite rate; they found that the combined impact of the number of stalling events, the average stalling duration, and the average bitrate have to be considered when designing a model to estimate the user engagement. While in Reference 26 it has shown a strong mapping where user engagement can be correlated to stalling ratio and a negative correlation between user engagement and quality switches in the context of non‐mobile scenarios. As a further exploration in the study of customer engagement behavior, dynamic interactivity, and user experience, the first work that studies the popularity of video content is done by Chatzopoulou et al, 27 who have found that video popularity has high correlation with four metrics that are: view count, favorites, comments, and ratings.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation